A Smartphone-Based Genotyping Method for Hepatitis B Virus at Point-of-Care Settings. (April 2017) - Jiang, Huiqin; Wu, Di; Song, Liuwei; Yuan, Quan; Ge, Shengxiang; Min, Xiaoping; Xia, Ningshao; Qian, Shizhi; Qiu, Xianbo
We reported a rapid, convenient, and easy-to-use genotyping method for hepatitis B virus (HBV) based on the smartphone at point-of-care (POC) settings. To perform HBV genotyping especially for genotypes A, B, C, and D, a smartphone is used to image and analyze a one-step immunoassay lateral flow strip functionalized with genotype-specific monoclonal antibodies (mAbs) on multiple capture lines. A light-emitting diode (LED) positioned on the top of the lateral flow strip is used to shine the multiple capture lines for excitation. Fluorescence detection is obtained with a smartphone whose camera is used to take the fluorescent images. An intelligent algorithm is developed to first identify each capture line from the fluorescent image and then determine the HBV genotype based on a genotyping model. Based on the pattern of the detection signal from different samples, a custom HBV genotyping model is developed. Custom application software running on a smartphone is developed with Java to collect and analyze the fluorescent image, display the genotyping result, and transmit it if necessary. Compared with the existing methods with nucleic acid analysis, more convenient, instant, and efficient HBV genotyping with significantly lower cost and a simpler procedure can be obtained with the developed smartphone POC HBV genotyping method.